Studio sui NEETs. Credenze, paure e percezioni delle giovani generazioni stigmatizzate - Marco Schiavetta (Phenomena Journal)
The paper presents the results of qualitative field research about the phenomenon of NEETs - Not (engaged) in Education, Employment or Training - investigated with the constructivist Grounded Theory methodology. The research, which involved 82 young people aged between 18 and 24 years, began in November 2015 and ended with the analysis of data collected in December 2018. In line with the methodological indications of the constructivist Grounded Theory (GT) (Charmaz, 2000, 2006, 2014), field research was immediately accompanied by open coding, using all that was useful for saturation of the categories. The constant critical reflection, conducted throughout the process of my research, has led to detect and define 3 core categories that are fundamental to the definition of a substantive theory. The permanent orientation emerges as a social need because it promotes and increases the psychological well-being of NEETs. The comparison between the “initial” questions of research and the 3 core categories, conceptually valid, allowed me to start the process of focusing and analyzing the possible correlations. Correlations capable of supporting a scientifically strong definition, for the proposal of a substantive theory, emerging from the three initial questions of the research. 1. How do you “selfassess” NEETs with respect to the world of work? Psychological area: to understand the characteristics of the NEET individual. How to contribute to its identity awareness about operating (occupying and acting) a role. To train him/her to reflect on his/her own interests, in accordance with his/her own authentic purposeful Self (Di Fabio, 2014).